B4galnt2-mediated host glycosylation influences the susceptibility to Citrobacter rodentium infection - Suwandi, Abdulhadi; Alvarez, Kris Gerard; Galeev, Alibek; Steck, Natalie; Riedel, Christian U.; Puente, José Luis; Baines, John F.; Grassl, Guntram A. (Frontiers in Microbiology, 2022)
Histo-blood group antigens in the intestinal mucosa play important roles in host-microbe interactions and modulate the susceptibility to enteric pathogens. The B4galnt2 gene, expressed in the GI tract of most mammals, including humans, encodes a beta-1,4-N-acetylgalactosaminyltransferase enzyme which catalyzes the last step in the biosynthesis of the Sd(a) and Cad blood group antigens by adding an N-acetylgalactosamine (GalNAc) residue to the precursor molecules. In our study, we found that loss of B4galnt2 expression is associated with increased susceptibility to Citrobacter rodentium infection, a murine model pathogen for human enteropathogenic Escherichia coli. We observed increased histopathological changes upon C. rodentium infection in mice lacking B4galnt2 compared to B4galnt2-expressing wild-type mice. In addition, wild-type mice cleared the C. rodentium infection faster than B4galnt2-/- knockout mice. It is known that C. rodentium uses its type 1 fimbriae adhesive subunit to bind specifically to D-mannose residues on mucosal cells. Flow cytometry analysis of intestinal epithelial cells showed the absence of GalNAc-modified glycans but an increase in mannosylated glycans in B4galnt2-deficient mice compared to B4galnt2-sufficient mice. Adhesion assays using intestinal epithelial organoid-derived monolayers revealed higher C. rodentium adherence to cells lacking B4galnt2 expression compared to wild-type cells which in turn was reduced in the absence of type I fimbriae. In summary, we show that B4galnt2 expression modulates the susceptibility to C. rodentium infection which is partly mediated by fimbriae-mannose interaction.